2006
DOI: 10.1136/thx.2005.051284
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphism of tumour necrosis factor  -308 gene promoter and asthma: a meta-analysis

Abstract: Background: Asthma is a complex polygenic disease in which gene-environment interactions are important. The gene encoding tumour necrosis factor alpha (TNFa) is one of several candidate loci for asthma pathogenesis and is highly polymorphic. A number of studies have investigated the polymorphism of TNFa-308 gene promoter (substitution GRA, designated as TNF1 and TNF2) in relation to asthma susceptibility in different populations. However, the results of individual studies have been inconsistent. Methods: To ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 38 publications
1
43
0
3
Order By: Relevance
“…Statistically, there is increased power in studying the equivalent number of individuals in case-control association studies than in family-based studies [18]. However, small population sizes, population stratification, phenotype heterogeneity and varied environmental exposure are often blamed for negative replication of initially positive associations [10,29]. The current study has some advantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistically, there is increased power in studying the equivalent number of individuals in case-control association studies than in family-based studies [18]. However, small population sizes, population stratification, phenotype heterogeneity and varied environmental exposure are often blamed for negative replication of initially positive associations [10,29]. The current study has some advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic risk factors for asthma have often differed among different populations [10]. This may be caused by phenotypic heterogeneity, different ethnicity and linkage disequilibrium (LD) patterns.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 10 meta-analyses of specific gene variants for asthma [1,2,3,4,5,6,7,8,9,10]. They evaluated single nucleotide polymorphisms (SNPs) for 5 genes [tumor necrosis factor alpha ( TNFA , n = 2 meta-analyses), β 2 -adrenergic receptor ( B2AR , n = 4 meta-analyses), a disintegrin and metalloprotease 33 ( ADAM33 , n = 2 meta-analyses), CD14 , and leukotriene C4 synthase (LTC4S) ].…”
Section: Resultsmentioning
confidence: 99%
“…A possible role of the TNF-␣ Ϫ308GϾA allelic variant has been investigated in several diseases. The TNF-␣ Ϫ308A allele was positively associated with manifestations of inflammatory processes such as septic shock (16 ), cerebral malaria (17 ), Crohn disease (18 ), and asthma (19 ); however, not all studies confirmed these associations (20 -23 ). No significant association or controversial results have been reported in studies investigating the role of the TNF-␣ Ϫ308AϾG allelic variant in coronary artery disease (24 -26 ), type 2 diabetes (27 ), or hypertension (28,29 ).…”
mentioning
confidence: 98%